2000
DOI: 10.1097/00006565-200004000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of family member presence during pediatric resuscitations in the emergency department: Effects of personal experience

Abstract: Opinions on FMP are strongly influenced by experience with this practice. Emergency department personnel with prior exposure to family member presence during resuscitations favor this activity. Biases by EDP lacking experience with FMP may limit its introduction into unfamiliar institutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
66
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(69 citation statements)
references
References 14 publications
2
66
0
1
Order By: Relevance
“…6 Thus, similar to our study, a large discrepancy between the attitudes of nurses and physicians was discovered, and both groups did not support family presence during active resuscitation. 6 Another study found that in environments where parents were regularly invited into pediatric resuscitations, the staff had a much more favorable opinion than in institutions that rarely allowed parental presence, 5 suggesting that a ''try it, you'll like it'' phenomenon may exist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Thus, similar to our study, a large discrepancy between the attitudes of nurses and physicians was discovered, and both groups did not support family presence during active resuscitation. 6 Another study found that in environments where parents were regularly invited into pediatric resuscitations, the staff had a much more favorable opinion than in institutions that rarely allowed parental presence, 5 suggesting that a ''try it, you'll like it'' phenomenon may exist.…”
Section: Discussionmentioning
confidence: 99%
“…Previously conducted surveys and observational studies have demonstrated that most parents prefer to stay with their children during procedures occurring in EDs. [1][2][3][4][5] Parents also believe that they should participate in the decision to be present and that the physician should not unilaterally decide it. 4 Health care providers are much less willing to allow parental presence than parents would prefer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,3,12 Physicians and nurses reported that they would feel increased anxiety about their performance because they would be critiqued. 6,12,13 Health professionals also reported that if families are present they will feel an added pressure to prolong resuscitation unnecessarily. 1,12 It is evident that many health professionals have strong concerns about family presence.…”
Section: Disadvantages Of Family Presencementioning
confidence: 99%
“…[11][12][13] Recent reviews and studies promote providing the option of parental presence even for very invasive procedures. [14][15][16][17] Yet, some parents may not be emotionally capable of remaining present for certain procedures and should not be forced to stay. 17 Health care workers must be prepared to initiate discussions regarding parental presence for pediatric procedures.…”
mentioning
confidence: 99%